Axon growth inhibition by RhoA/ROCK in the central nervous system - Fujita, Yuki; Yamashita, Toshihide (Frontiers in Neuroscience, 2014)
Rho kinase (ROCK) is a serine/threonine kinase and a downstream target of the small GTPase Rho. The RhoA/ROCK pathway is associated with various neuronal functions such as migration, dendrite development, and axonal extension. Evidence from animal studies reveals that RhoA/ROCK signaling is involved in various central nervous system (CNS) diseases, including optic nerve and spinal cord injuries, stroke, and neurodegenerative diseases. Given that RhoA/ROCK plays a critical role in the pathophysiology of CNS diseases, the development of therapeutic agents targeting this pathway is expected to contribute to the treatment of CNS diseases. The RhoA/ROCK pathway mediates the effects of myelin-associated axon growth inhibitors—Nogo, myelin-associated glycoprotein (MAG), oligodendrocyte-myelin glycoprotein (OMgp), and repulsive guidance molecule (RGM). Blocking RhoA/ROCK signaling can reverse the inhibitory effects of these molecules on axon outgrowth, and promotes axonal sprouting and functional recovery in animal models of CNS injury. To date, several RhoA/ROCK inhibitors have been under development or in clinical trials as therapeutic agents for neurological disorders. In this review, we focus on the RhoA/ROCK signaling pathway in neurological disorders. We also discuss the potential therapeutic approaches of RhoA/ROCK inhibitors for various neurological disorders.